2020
DOI: 10.3389/fmed.2020.00463
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Increases the Efficacy of Oxygen Utilization of Colonic Mitochondria and Uncouples Hepatic Mitochondria in Tissue Homogenates From Healthy Rats

Abstract: Background: Studies suggest that indomethacin (Indo) exhibits detrimental changes in the small intestine (microvascular disorder, villus shortening, and epithelial disruption), mainly due to mitochondrial uncoupling. The effects of Indo on colon and liver tissue are unclear. The aim of this study was to determine the effects of Indo on mitochondrial respiration in colonic and hepatic tissue. Methods: Mitochondrial oxygen consumption was assessed in colon and liver homogenates from healthy rats. Homogenates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, Truse et al [87] also proved that melatonin could significantly regulate gastric microcirculatory oxygenation, which may be a new aspect of the protective effect. Herminghaus et al [88] found that indomethacin significantly affects mitochondrial function in healthy rats, which is organ-specific and concentrationdependent, and its effect should be further confirmed by in vivo studies. A recent study found that mitochondrial transplantation may be valuable in restoring organ function to critically ill patients [89].…”
Section: Mitochondria-guided Treatmentsmentioning
confidence: 95%
“…In addition, Truse et al [87] also proved that melatonin could significantly regulate gastric microcirculatory oxygenation, which may be a new aspect of the protective effect. Herminghaus et al [88] found that indomethacin significantly affects mitochondrial function in healthy rats, which is organ-specific and concentrationdependent, and its effect should be further confirmed by in vivo studies. A recent study found that mitochondrial transplantation may be valuable in restoring organ function to critically ill patients [89].…”
Section: Mitochondria-guided Treatmentsmentioning
confidence: 95%